Experimental and Numerical Evaluation of Shear Strength of Directly and Indirectly Loaded Flanged Recycled Self-Compacted Reinforced Concrete Deep Beams - Thamer Hussein Amer Alhussein; Jamal Abdul Samad Khudhair (Journal of Engineering)
Experimental and numerical investigations of the behavior of directly and indirectly loaded flanged reinforced concrete (RC) deep beams cast with self-compacted concrete (SCC) containing recycled concrete as coarse aggregate (RCA) were conducted in this research. Seventeen RC deep flanged beams were designed to fail in shear. These beams were divided into three groups: twelve indirectly loaded beams without shear reinforcement; three directly loaded beams without stirrups; and two indirectly loaded beams with vertical stirrups. These beams were also classified according to the RCA ratio and shear span-to-effective depth (a/d) ratio, which will be detailed later. The RCA ranged from 0% to 75%, while the a/d ratio was taken as 1.0, 1.35, and 1.7. Experimental results show that the use of RCA reduces the cracking and ultimate capacities, and this finding complies with the conclusions of several research studies in the literature as will be detailed later. It was observed that beams with higher RCA exhibited higher deflection, strain, and crack width. Furthermore, by increasing the a/d ratio, the ultimate load was decreased due to the lower contribution of arch action shear transfer in the beam. A web reinforcement spaced at 100 mm and 50 mm increases the ultimate load by 35% and 48%, respectively. Strut and tie model (STM) presented by the American Concrete Institute (ACI) 318-14 and the American Association of State Highway and Transportation Officials (AASHTO LRFD 2012) was used to predict the ultimate shear capacity of the beams. STM predicted lower beam capacity than the experimental result. The ultimate strength calculated using ACI318-14 and AASHTO LRFD 2012 was on average 38% and 52% lower than the experimental data, respectively, which reflects the conservative nature of this approach. Finally, 3D finite element models were created to investigate the responses of the beams. The FE results showed very good agreement with the experimental data, where FE-predicted shear capacities were on average 9% higher than the experimental results.